The meaningful writing project: learning, teaching, and writing in higher education - Eodice, Michele, author; Geller, Anne Ellen, author; Lerner, Neal, author; Utah State University Press, publisher (Colorado State University. Libraries, 2016)
Unprecedented look into the writing projects students find meaningful. The results of a three-year study consisting of surveys and interviews of seniors and faculty across three diverse institutions that consider the qualities of experiences, students' perceptions of their experiences, and analyze instructors' perspectives on assignment design/delivery .--Provided by publisher.
The meaning of the meaningful writing project -- Agency and the meaningful writing project -- Engagement and the meaningful writing project -- Learning for transfer and the meaningful writing project -- Meaningful writing happens when -- Some conclusions -- Appendix A: Common data set -- Appendix B: Student survey -- Appendix C: Student recruitment email -- Appendix D: Undergraduate and graduate research assistants -- Appendix E: Student interview questions -- Appendix F: List of codes -- Appendix G: Interview questions for faculty.
Keywords: Report writing -- Study and teaching -- United States -- Evaluation; English language -- Rhetoric -- Study and teaching -- United States -- Evaluation